Magnetron sputtering onto nonionic surfactant for 1-step preparation of metal nanoparticles without additional chemical reagents - Sergievskaya, Anastasiya; Alem, Halima; Konstantinidis, Stephanos (Nanotechnology, 2023)
Plasma-based sputtering onto liquids (SoL) is a straightforward approach for synthesizing small metal nanoparticles (NPs) without additional stabilizing reagents. In this work, nonionic surfactant Triton X-100 was used for the first time as a host liquid for the SoL process and the production of colloidal solutions of gold, silver and copper NPs was demonstrated. The average diameter of spherical Au NPs lies in the range from 2.6 to 5.5 nm depending on the conditions. The approach presented here opens the pathway to the production of concentrated dispersions of metal NPs of high purity that can be dispersed in water for future usage, therefore extending further the reach of this synthesis pathway.